The Mediterranean dish : 120 bold and healthy recipes you'll make on repeat - Karadsheh, Suzy; Puckett, Susan, 1956- (Clarkson Potter/Publishers, 2022)
"The highly anticipated debut cookbook from Suzy Karadsheh, founder of the blog The Mediterranean Dish, with more than 120 recipes for bright and flavorful Mediterranean diet-inspired meals. What began as one of the first online Mediterranean food blogs in 2014 has now blossomed into the long-awaited cookbook from Suzy Karadsheh who now has the most visited Mediterranean food blog. The Mediterranean Dish brings cross-culturally inspired dishes from throughout the Mediterranean into American home kitchens. Suzy's approach is practical and weeknight easy--a mom of two teenage daughters, Suzy is well versed in having to make dinner on the fly. Born in Egypt, Suzy lived in Michigan and Des Moines with her Palestinian husband before moving to Atlanta. Suzy's recipes reflect the rich and complex history of the Mediterranean and the Middle East from Tunisia to Greece and Jordan to southern Spain. Her winning combination of approachable instructions, friendly voice, reliable recipes, and simple assemblies create a package that is sure to thrill her hungry followership"--